Development and evaluation of stability of gel formulation containing Ageratum conyzoides extract - Sirikunya Sayompark,; Sopita Tangpiriyavaree,; Yupa Khongprik,; Khanitta Meepradit, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Ageratum conyzoides or ‘Billy Goat Weed’ is a weed distributed in many tropical and subtropical countries. It is widely utilized in traditional medicine by various cultures worldwide. The leaf, stem, root and flower of A. conyzoides was used to evaluate its chemical profile. Their extract exhibit a wide range of biological and pharmacological activities such as antiinflammatory, anti-allergic, analgesic, antifungal, and anti-bacterial activities have been recorded. The objectives of the study were to evaluate the phytochemical screening tests of ethanolic extract of A. conyzoides and finally, the A. conyzoides extract was developed in Gel formulation. The A. conyzoides gel formulation was studied the stability at 45°C and heating/cooling condition, and then its appearance, viscosity, and pH value were determined. The presence phytochemical components of A. conyzoides extract include alkaloids, tannins, flavonoids and phenols. The AC-6 formulation was showed good physical properties: appearance, viscosity, and pH value by comparing it with marketed Diclofenac gel. The further study should be evaluated for anti-inflammatory and analgesic potency by animal paradigms, which may be helpful in developing novel new drugs.